Tendencies of further development of social legislation system in Ukraine - Saynetsky, Oleg (Київський національний університет імені Тараса Шевченка, 2019)
In the article the specifics of prospects for further development of systematization of social legislation in Ukraine are analyzed. The list of tendencies of further development of systematization of social legislation in Ukraine is formulated. The content and meaning of each of them are disclosed.

У статті проаналізовано специфіку перспектив подальшого розвитку систематизації соціального законодавства в Україні. Сформульовано перелік тенденцій подальшого розвитку систематизації соціального законодавства в Україні. Розкрито зміст і значення кожної з них.
Тенденції подальшого розвитку систематизації соціального законодавства в Україні
Keywords: trends; legal regulation; systematization; social legislation; social law.; тенденції; правове регулювання; систематизація; соціальне законодавство; соціальне право.